PENGARUH DISIPLIN DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT. ESA GARDA PRATAMA JAKARTA SELATAN - Handayani, Meisuri; Andi, Dede (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of discipline and the physical work environment on employee performance at PT Esa Garda Pratama, South Jakarta. The research method used is a quantitative method. The population in this study was 50 people. The sampling technique used a saturated sample using a sample of 50 people. The data analysis method in this research uses the IBM SPSS version 26 application, including validity test, reliability test, classical assumption test, multiple linear regression test, correlation coefficient test, coefficient of determination test and hypothesis test. The results of this research, namely the variables Discipline, Physical Work Environment and Employee Performance, obtained the multiple regression equation Y = 4.817 + 0.267X1 + 0.629X2+ e. The regression coefficient value on the employee performance variable is 4.817, concluding that if Discipline (X1) and Physical Work Environment (X2) are constant (have not changed) then the performance consistency value (Y) is 4.817. The results of the t test show a positive and significant influence of discipline on employee performance based on the table that tcount is 7.451 > t table 2.011 or significantly 0.000 < 0.05. Thus, partially there is a positive and significant influence of discipline (X1) on employee performance (Y). Based on the table, tcount is 7.331 > ttable 2.011 with a significance of 0.000 <0.05, thus partially there is a positive and significant influence of the Physical Work Environment (X2) on Employee Performance (Y) and the results of the simultaneous f test calculation show an f-count value of 7.972 > f -table 2,800 and uses a significance limit of 0.001 < 0.05. It can be said that the hypothesis states that the variables Discipline (X1), Physical Work Environment (X2) have an influence on employee performance (Y) simultaneously.